177k views
0 votes
(1−xm−n)−1+(1−xn−m)−1​

User Dom Farr
by
6.0k points

1 Answer

6 votes

Answer:

Solution below.

Explanation:

This question requires the concept of Order of Operations and Factorisation.

First, we will evaluate the expressions in the brackets first.


(1 - xm - n) - 1 + (1 - xn - m) - 1 \\ = 1 - xm - n - 1 + 1 - xn - m - 1 \\

Next we will cancel out all the "1"s as 1 - 1 + 1 - 1 = 0

That leaves us with:


- xm - n - xn - m

Now we can factorise them.


- xm - n - xn - m \\ = - x(m + n) - n - m \\ = - x(m + n) - 1(n + m) \\ = ( - x - 1)(m + n)

Note: m + n = n + m

User Lowerends
by
5.7k points